Diabetes mellitus: avaliação do conhecimento de cirurgiões-dentistas em municípios de três estados brasileiros - Yarid, Sérgio Donha; Del Rey, Natali Cardoso Cafeseiro; Santos, Adrielle Mangabeira; Garbin, Cléa Adas Saliba [UNESP]; Sumida, Doris Hissako [UNESP] (My University, 2011)
Introduction: Pathological changes in the bucal cavity associated with Diabetes mellitus (DM) may include gingivitis, periodontal disease, salivary gland dysfunction and xerostomia (dry mouth), susceptibility to bucal infections, burning mouth syndrome, and altered taste. Objective: This study assessed the technical and scientific knowledge of dentists working in primary care in the National Health System (SUS) on the DM. Material and method: The study was conducted in the municipalities of Birigui-SP, Maringá-PR and TrêsLagoas-MS, with the participation of 76 dentists working in the SUS primary care system.These professionals agreed to answer to a questionnaire developed for this study and the results of the questions were submitted to a quantitative analysis. Result: Showed that 94.7% were in contact with diabetic patients; 97.4% know what is DM; about other types of DM, 77.6% said they know, the most mentioned (by 55.9%) was the gestational DM. The DM2 was indicated as the most prevalent by 59.2%; the normal range of fasting blood glucose level was quoted correctly by 2.6% of the participants; obesity was reported by 98.7% of participants as a risk factor for DM; 96.0% stated correctly what are the main signs and symptoms related to Diabetes; periodontal disease was reported by 92.1% as an bucal manifestation in diabetic patients. Conclusion: The dentist needs to develop specific knowledge about DM, being able to identify normal levels of blood glucose and ready to identify and meet the bearer of DM.

Introdução: Alterações patológicas na cavidade bucal associadas ao Diabetes mellitus (DM) podem incluir gengivite, doença periodontal, disfunção da glândula salivar (xerostomia), suscetibilidade para infecções bucais, síndrome de ardência bucal e alteração do paladar. Objetivo: Verificar o conhecimento técnico-científico de cirurgiões-dentistas que atuam na atenção básica do Sistema Único de Saúde (SUS) sobre o DM. Material e método: O estudo foi realizado nos municípios de Birigui-SP, Maringá-PR e Três Lagoas-MS, e os profissionais que consentiram (n = 76) responderam a um questionário sobre o tema. Os dados foram analisados quantitativamente. Resultado: Os dados obtidos junto a estes profissionais mostram que a maioria (94,7%) prestou consultas odontológicas a pacientes portadores de Diabetes; muitos (97,4%) sabem o que é o DM; sobre outros tipos de DM, 77,6% afirmaram que conhecem, sendo o mais citado – por 55,9% dos profissionais – o DM Gestacional; o DM2 foi apontado como o mais prevalente por 59,2%. A faixa normal de glicose em jejum foi citada corretamente por 2,6% dos participantes. A obesidade foi apontada por 98,7% dos participantes como fator de risco para o DM. Grande parte (96,0%) assinalou corretamente quais os principais sinais e sintomas que levam à suspeita de DM. A doença periodontal foi apontada por 92,1% como manifestação bucal do paciente portador de DM. Conclusão: Os cirurgiões-dentistas devem desenvolver um conhecimento específico sobre o DM, estando atentos aos níveis normais de glicemia e prontos para identificar e atender o portador de DM.
Diabetes mellitus: evaluation of dentists’ knowledge in cities of three Brazilian’s states
Keywords: Diabetes mellitus; Buccal manifestations; Dental care; Diabetes mellitus; Manifestações bucais; Assistência odontológica